Increased Oral Bioavailability of Piperine from an Optimized Piper nigrum Nanosuspension - Zafar, Fatiqa; Jahan, Nazish; Khalil-Ur-Rahman; Bhatti, Haq Nawaz (Planta Medica, 2019)
The aim of the present study was to enhance the pharmaceutical potential and oral bioavailability of piperine, which is the bioactive constituent of Piper nigrum, using the nanosuspension approach. Nanoprecipitation, which is a simple and reproducible process, was used for nanosuspension formulation. To prepare a pharmaceutical-grade nanosuspension with the required particle size, important formulation parameters (amount of plant extract, concentration of stabilizer, and antisolvent-to-solvent ratio) were optimized using the central composite design of response surface methodology. The optimized nanosuspension was characterized using scanning electron microscopy, atomic force microscopy, Fourier transform infrared spectroscopy, and in vitro dissolution testing as well as by measuring the zeta potential. In vivo pharmacokinetic studies were conducted to determine the bioavailability of the prepared nanosuspension. Results of the optimization study indicated that 0.13% plant extract, 0.25% stabilizer, and an antisolvent-to-solvent ratio of 10.0 were the best parameters to obtain a homogeneous nanosuspension with the required particle size. The optimized nanosuspension demonstrated a mean particle size, polydispersity index, and zeta potential of 172.5 nm, 0.241, and − 16.6 mV, respectively. The results of the characterization studies illustrated that the nanosuspension was in the nanometer size range and had good surface morphology. The optimized nanosuspension showed a better dissolution rate and a 3.65-fold higher oral bioavailability for the P. nigrum nanosuspension than its coarse suspension. The present outcomes clearly demonstrated that to obtain an effective therapeutic potential, nanoformulation of medicinal plants is a better alternative than conventional dosage forms.
Keywords: nanosuspension; bioavailability; piperine; pharmacokinetics; Piper nigrum; Piperaceae